Video animation in coordination system to improve students’ cognitive ability - Zahra Firdaus; Siti Zubaidah; M. Munzil (University of Muhammadiyah Malang, 2024)
The biological concept has a broad scope and requires the visualisation of bioprocesses to provide complex understanding. Learning media can help visualise bioprocesses to enhance students’ cognitive abilities. The study aimed to develop, test the practicality, and test the effectiveness of video animation in improving grade XI high school students’ und erstanding of the coordination system. This study involved 66 high school students in grade XI of the science department at State Senior High School 2 Malang, Indonesia. This research used the Lee & Owens Multimedia-Based Instructional Design method, which consisted of analysis, design, development, implementation, and evaluation stages. In the evaluation stage, we conducted face validity by media experts and content validity by material experts, successively getting results of 97% and 100%. Then, the concurrent validity test was obtained from student assessments of the media interface with a result of 97%, the user-friendly with a result of 100%, and the appropriateness of the material with a result of 95%. In the final stage, construct validity was carried out through an effectiveness test using a quasi-experimental design with a pretest-posttest control group design. Data analysis was performed using the Independent T-test, with the results showing a significance of 0.006 < 0.05, which showed a significant difference in the average post-test between the control and experimental classes. The average score in the experimental class increased from 76.32 to 89.03, but the control class increased from 76.38 to 84.56. The results showed that the video animation media effectively improved students’ abilities. Therefore, this learning media can be a recommendation in the learning coordination system.